Transcriptome‐wide association study reveals candidate causal genes for lung cancer. Issue 7 (9th December 2019) - Bossé, Yohan; Li, Zhonglin; Xia, Jun; Manem, Venkata; Carreras‐Torres, Robert; Gabriel, Aurélie; Gaudreault, Nathalie; Albanes, Demetrius; Aldrich, Melinda C.; Andrew, Angeline; Arnold, Susanne; Bickeböller, Heike; et al.
Abstract : We have recently completed the largest GWAS on lung cancer including 29, 266 cases and 56, 450 controls of European descent. The goal of our study has been to integrate the complete GWAS results with a large‐scale expression quantitative trait loci (eQTL) mapping study in human lung tissues ( n = 1, 038) to identify candidate causal genes for lung cancer. We performed transcriptome‐wide association study (TWAS) for lung cancer overall, by histology (adenocarcinoma, squamous cell carcinoma and small cell lung cancer) and smoking subgroups (never‐ and ever‐smokers). We performed replication analysis using lung data from the Genotype‐Tissue Expression (GTEx) project. DNA damage assays were performed in human lung fibroblasts for selected TWAS genes. As expected, the main TWAS signal for all histological subtypes and ever‐smokers was on chromosome 15q25. The gene most strongly associated with lung cancer at this locus using the TWAS approach was IREB2 ( p TWAS = 1.09E−99), where lower predicted expression increased lung cancer risk. A new lung adenocarcinoma susceptibility locus was revealed on 9p13.3 and associated with higher predicted expression of AQP3 ( p TWAS = 3.72E−6). Among the 45 previously described lung cancer GWAS loci, we mapped candidate target gene for 17 of them. The association AQP3 ‐adenocarcinoma on 9p13.3 was replicated using GTEx ( p TWAS = 6.55E−5). Consistent with the effect of risk alleles on gene expression levels, IREB2 knockdown and AQP3 overproduction promote endogenous DNA damage. These findings indicate genes whose expression in lung tissue directly influences lung cancer risk. Abstract : What's new? Genome‐wide association studies identify genomic loci associated with certain cancers, but identifying the causal genes within these loci remains a major challenge. Here the authors performed a large transcriptome‐wide association study (TWAS) for lung cancer and found on chromosome 15 the iron‐responsive element‐binding protein 2 as the most likely target for all histological subtypes. They also identified a new susceptibility locus for lung adenocarcinoma on chromosome 9 with aquaporin 3 as the candidate causal gene, demonstrating how TWAS can refine the biological interpretation of genomic association studies.